2018
DOI: 10.1093/infdis/jiy227
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Oral JNJ-53718678 in Healthy Adult Volunteers Challenged With Respiratory Syncytial Virus: A Placebo-Controlled Study

Abstract: ClinicalTrials.gov: NCT02387606; EudraCT number: 2014-005041-41.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 27 publications
4
41
0
Order By: Relevance
“…No significant differences in RT-qPCR AUC were observed between the 200-mg and 350-mg dose groups, although it should be noted that the study was not designed to assess differences in treatment effect between the two doses. The terminal half-life of RV521 (8.54 to 9.35 h) is shorter than or comparable to that reported for other studied anti-RSV compounds (33 to 35 h for GS-5806 [12], 63 h for ALS-008176 [19], and 6.5 to 10.5 h for JNJ-53718678 [20]), which may offer advantages, especially in relation to pediatric dosing, in avoiding accumulation and potential toxicity. The safety and PK of RV521 will be assessed in infants hospitalized with RSV infection in a planned phase 2a study.…”
Section: Figsupporting
confidence: 57%
See 3 more Smart Citations
“…No significant differences in RT-qPCR AUC were observed between the 200-mg and 350-mg dose groups, although it should be noted that the study was not designed to assess differences in treatment effect between the two doses. The terminal half-life of RV521 (8.54 to 9.35 h) is shorter than or comparable to that reported for other studied anti-RSV compounds (33 to 35 h for GS-5806 [12], 63 h for ALS-008176 [19], and 6.5 to 10.5 h for JNJ-53718678 [20]), which may offer advantages, especially in relation to pediatric dosing, in avoiding accumulation and potential toxicity. The safety and PK of RV521 will be assessed in infants hospitalized with RSV infection in a planned phase 2a study.…”
Section: Figsupporting
confidence: 57%
“…Although cross-study comparisons of data are inherently limited, the observed safety profile of RV521 seems to compare favorably with that of other anti-RSV agents (19,20). PK data from the current study suggest that RV521 200 mg and 350 mg are effective therapeutic doses in adult subjects, both resulting in significant improvements compared with placebo in primary and secondary viral load and disease severity endpoints.…”
Section: Figmentioning
confidence: 71%
See 2 more Smart Citations
“…Fusion inhibitors GS-5806 (presatovir) and JNJ-53718678, developed by Gilead Sciences and Janssen Pharmaceuticals, respectively, have both performed well in phase II double-blind, placebo-controlled, human-challenge studies. Oral administration of either compound led to a reduction in viral load and disease severity among healthy adults experimentally infected intranasally with a clinical isolate of RSV 143,144 . The participants were administered the fusion inhibitors either 5 days after inoculation or at the time of a positive test for RSV, demonstrating that these compounds could be used for treatment of an upper respiratory tract infection if administered soon after infection.…”
Section: Wwwnaturecom/nrmicromentioning
confidence: 99%